Peran Resiliensi Sebagai Mediator Pada Hubungan Afek Negatif Dan Keterikatan Kerja - Angelina, Stephanie; Y.S. Suyasa, P. Tommy (Fakultas Ekonomi Universitas Gresik, 2023)
This research was conducted to see the role of resilience as a mediating variable in negative affect and work engagement. This research used quantitative research method such as non-probability sampling technique with convenience sampling on 110 employees in store division at PT X, which is a retail company. Participants characteristics in this research are having at least one year of service and minimum education of SMA/SMK. The questionnaire was filled out by the research participants by online and contained of three measuring instruments, namely the Utrecht Work Engagement Scale (UWES-9) by Schaufeli et al. (2006) to measure work engagement, the Connor-Davidson Resilience Scale (CD-RISC) ) developed by Connor & Davidson (2003) to measure resilience, and 10 negative items from the Positive and Negative Affect Schedule (PANAS) developed by Watson & Clark (1988) to measure negative affect. Data processing was carried out using SPSS version 27.0 and additional program named PROCESS Macro by Hayes (2018) to test the role of mediation. The results showed that negative affect and work engagement had a significant negative relationship (p<0.01). The results of subsequent tests found that resilience acts as a partial mediation in the negative affect relationship and engagement with a significant mediating role with a total effect of -0.377. Thus employee resilience can be a factor affecting work engagement and resilience can also be influenced by employee negative affect